Effectiveness and Safety of Iguratimod in Treating Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis - Pu, Jincheng; Wang, Xuan; Riaz, Farooq; Zhang, Tongyangzi; Gao, Ronglin; Pan, Shengnan; Wu, Zhenzhen; Liang, Yuanyuan; Zhuang, Shuqi; Tang, Jianping (Frontiers in Pharmacology, 2021)
Objectives: We aimed to assess the effectiveness and safety of iguratimod (IGU) in treating primary Sjögren’s syndrome (pSS) by meta-analysis. Methods: Eight databases and two clinical trial websites were searched from conception to August 10, 2020, for relevant randomized controlled trials (RCTs) on outcomes of patients with pSS treated with IGU. Revman 5.4 was used for statistical analysis and creating plots. Results: A total of 1,384 patients with pSS from 19 RCTs were included in this meta-analysis. Pooled results demonstrated that patients treated with IGU + hydroxychloroquine (HCQ) + glucocorticoid (GC) showed significant differences in erythrocyte sedimentation rate (ESR), rheumatoid factor (RF) level, platelet (PLT) count, immunoglobulin G (IgG) level, salivary flow rate, Schirmer’s test result, EULAR Sjögren’s Syndrome Patient Reported Index (ESSPRI), EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI), and efficacy rate (P ≤ 0.01) compared to patients treated with HCQ+GC. Compared to treatment with HCQ and GC, co-administration of IGU with GC showed significant differences in ESR and RF level (P ≤ 0.01); however, no significant differences were noted in IgG level. Conversely, the IgG level showed a significant improvement in the IGU+HCQ+GC group compared to the HCQ+GC group. The results of safety analysis revealed that seven trials showed no significant differences in adverse events (AEs) between the IGU+HCQ+GC and HCQ+GC groups (P = 0.15). Although no severe AEs were noted, gastrointestinal discomfort was the most common AE in the IGU group. No significant differences in AEs were observed between the IGU+GC and HCQ+GC groups. Conclusion: IGU improved the clinical symptoms of patients with pSS, including inflammatory indicators (ESR, IgG and RF levels), PLT count, secretion function of the salivary and lacrimal glands (salivary flow rate and Schirmer’s test result), and disease indexes (ESSDAI and ESSPRI), when co-administered with HCQ+GC therapy without increasing the risks of AEs. Therefore, IGU can be considered as an effective and safe drug for clinical therapy of pSS. Considering the limitations of the present trials, more long-term, multicenter, and high-quality RCTs are required to assess the effectiveness and safety of IGU for treating patients with pSS.